Race, ethnicity, gender and other social characteristics as factors in health and health care disparities - Kronenfeld, Jennie Jacobs (Bingley, U.K. : Emerald Publishing Limited, 2020)
The contributors to this latest volume of Research in the Sociology of Health Care investigate race, ethnicity and gender as factors in health and health care disparities. Looking specifically at the factors that impact race and ethnicity in a US context, gender issues, hospitals and health care spending, and research from India. Chapters focus on linkages to health disparities among races, health experiences for incarcerated women and issues of hospital and health care spending.
Part 1 Race and Ethnicity in the US Context -- Chapter 1 The Impact of Racial Discrimination on Health Disparities among Asian Americans -- Chapter 2 Mental Health Disparities in Children of Caribbean Immigrants: How Racial/Ethnic Self-identification Informs the Association between Perceived Discrimination and Depressive Symptomatology -- Chapter 3 Healthcare Utilization, Diabetes Prevalence, and Comorbidities: Examining Sex Differences among American Indian and Alaska Native Peoples -- Chapter 4 ER Use among Older Adult RHC Medicare Beneficiaries in the Southeastern United States -- Chapter 5 Barriers to Healthcare Access for a Native American Tribe in the Gulf Coast Region of the United States -- Part 2 Gender -- Chapter 6 Hyperemesis Gravidarum: What to Expect when You are ExpectingNot! -- Chapter 7 Social Status and White Fragility: Gender and Socioeconomic Variations -- Chapter 8 The Intersection of Social Determinants of Health and Adverse Childhood Experiences for Incarcerated Women in San Bernardino County -- Part 3 Hospitals and Health-care Spending -- Chapter 9 Coercive Conformity: Does Mandated Reporting of Hospital Errors Improve Patient Safety? -- Chapter 10 It's the Politics, Stupid: Why More "Skin in the Game" Will Not Help Control US Healthcare Spending -- Part 4 Research from India -- Chapter 11 Exploring the Experiences of Family Caregivers of Older People in Residential Academic Campus of Higher Education in India -- Chapter 12 Why do AIDS Sufferers on Antiretroviral Therapy Die Early?Evidence from Jharkhand in India -- Index.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Public health -- Social aspects; Medical, Public Health; Medical sociology